HUBUNGAN PENGETAHUAN PEMILIHAN TERHADAP PERILAKU PENGGUNAAN SUPLEMEN KESEHATAN DI DESA BLIMBINGREJO MELALUI PROMOSI KESEHATAN DENGAN MEDIA LEAFLET - Nisa Oktadayana; Endang Setyowati; Yayuk Mundriyastutik (IJF (Indonesia Jurnal Farmasi), 2021)
Health supplements are medicinal preparations containing vitamins, minerals, and mutivitamins as a complement and nutritional needs. Inovercoming the covid-19 pandemic, preventive movement as one of the health behaviors, namely by living a healthy lifestyle, maintaining cleanliness, wearing masks, and intake of adequate nutrients to increase immunity. Of this study was to determine the relationship selection and behavior of use health supplements in village Blimbingrejo through health promotion with in the media leaflet. In this study use non-experimental observational research with one group pretest and posttest using a cross-sectional study approach. Non-probability sampling with purposive sampling or judgement sampling. The results of the pretest and posttest showed that in each given category there was a significant increase, namely the pretest value was higher than the posttest value. For the selection of supplements made by respondents and the behavior of using supplements were categorized as good after being given an understanding through leaflets. The results of the contigency coefficient test on the analysis of the behavior of using supplements pretest being given health promotion using leaflet media 0.346 ≥ 0.05 indicating that the hypothesis Ho (rejected). While the analysis of the relationship between selection knowledge and the behavior of using health suplements posttest 0.186 ≥ 0,05 indicated that the hypothesis Ho (rejected). Based on the results of the data it can be concluded that there is no relations between knowledge of selection and behavior in using health promotion using leaflet media. The results of the paired t-test unit for analysis of the relationship between selection knowledge and the behavior of using health suplements pretest and posttest obtained results of 0.000 0.05 there is a relationship knowledge selection using health supplements pretest and posttest being given health promotion with the media leaflet.Keywords: health supplements, knowledge selection, behavior health, and leaflet.